Effect of Partial Meat Replacement by Hibiscus sabdariffa By-Product and Pleurotus djamor Powder on the Quality of Beef Patties - Roberto Bermúdez; Esmeralda Rangel-Vargas; José M. Lorenzo; José A. Rodríguez; Paulo E. S. Munekata; Alfredo Teixeira; Mirian Pateiro; Leticia Romero; Eva M. Santos (Foods, 2023)
The effects of Hibiscus sabdariffa (roselle; Hs) by-product (2–5%) and Pleurotus djamor (pink oyster; Pd) powder (5–7.5%) as meat replacers on the physicochemical and sensorial properties of beef patties were analyzed. The addition of these non-meat ingredients significantly decreased moisture and increased fiber content, and did not affect the protein level of the product. The antioxidant effect of the roselle by-product was limited, while Pleurotus djamor favored the oxidation processes. The samples supplemented with roselle by-product and mushroom powder presented significantly lower microbial counts (total viable counts, enterobacteria, and Pseudomonas) than control, but texture and sensorial parameters were significantly affected. The patties darkened due to the presence of the Hibiscus by-product, while the color of the samples containing 5% Pleurotus djamor was hardly modified. These samples, together with the control samples, were the most sensorially appreciated. The addition of these ingredients provoked a decrease in texture parameters, being less pronounced in the samples with only 2% of roselle by-product. In spite of the good antimicrobial and antioxidant properties of Hibiscus by-products, its inclusion in meat should be moderate (2–2.5%) to avoid consumer rejection when Pleurotus djamor is also included in the formulation.